URGENSI SERTIFIKASI HALAL TERHADAP PRODUK PANGAN, BARANG DAN JASA SERTA OBAT-OBATAN DALAM KAITANNYA DENGAN PERLINDUNGAN KONSUMEN DI INDONESIA - Zeni Lutfiyah (Journal of Law, Society, and Islamic Civilization, 2016)
Indonesia is one country with the largest Muslim population in the world. This fact provides an opportunity for the circulation of halal products in Indonesia. In the era of free competition became one thing is very important to maintain the certainty of halal products circulating in Indonesia, and the certification is a process to obtain halal certification for products circulating in Indonesia. This certification is the primary aim of protecting consumers Muslims and provide outstanding product quality assurance and safeguarding public health. State as holder of the mandate of the people's sovereignty through various institution has the authority and is obliged to fulfill the right to security of its people consume. This has been realized in some rules that continue in effective as the Minister of Religion of the Republic of Indonesia No. 518 of 2001 which had been in place since 30 November 2001, even the MUI fatwa about food products, beverages and medicines halal has commenced since 1993. But the effective implementation of this regulation in the community has not been optimal. So that Muslims in Indonesia until now could not get inner peace in consuming food products as well as drug-medicine because until now kosher certification is voluntary (voluntary). However, since in legal OF RI Law No. 33 Year 2014 on halal product assurance, where the government requires halal certification for all products or services things in the Indonesian region be hope for protection and certainty of the legal status of halal food are systemic in Indonesia. Likewise, under Law No. 8, paragraph 1 of 1999 aboutconsumer protection (BFL) that businesses banned produce and or trade in goods or services that do not follow the rules to produce halal, as the statement contained in the label kosher certified by the agency that can in accountable. therefore arrangements regarding food security halal (JPH) needs to be set in one legislation that comprehensively products covering goods and / services related to food, beverage, medicine, cosmetics, chemical, biological products, and genetically modified products.Keywords : food, consumer protection, halal, certification